2020
DOI: 10.1002/app.49124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cellular uniformity on the necking propagation of foam injection Molded PP/HDPE blend parts

Abstract: Necking propagation (NP) is an important phenomenon that is facilitated by the superductility of many materials, although necking is often considered to be a type of unstable and heterogeneous deformation under tensile loading. In this study, the NP of samples produced with injection molding of polypropylene (PP) and high‐density polyethylene (HDPE) blends with or without a blowing agent was investigated by standard tensile testing, and the foam morphology and cellular structure were characterized with scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In this mechanism, the reduced cell size plays a key role. In the PP/HDPE system, the importance of the uniformity of the cellular structure in the deformation mechanism was also studied in depth by Zhou in several articles [51][52][53]. So, it is clear that the inclusion of the LCB-PP combined with foaming in our complex blend led to the formation of foams with a more ductile character.…”
Section: Mechanical Properties: Tensile Testsmentioning
confidence: 84%
See 1 more Smart Citation
“…In this mechanism, the reduced cell size plays a key role. In the PP/HDPE system, the importance of the uniformity of the cellular structure in the deformation mechanism was also studied in depth by Zhou in several articles [51][52][53]. So, it is clear that the inclusion of the LCB-PP combined with foaming in our complex blend led to the formation of foams with a more ductile character.…”
Section: Mechanical Properties: Tensile Testsmentioning
confidence: 84%
“…In our case, the elongation was not reduced when foaming, in fact, it was increased and this increment in ductility could lead to an increment in the toughness of the foams. This increment of elongation at break in foams when the LCB-PP content was raised to values above to those achieved for the solids with the same composition can be also explained by an optimized quality of the cellular structure [51][52][53].…”
mentioning
confidence: 81%
“…The effect of the size, shape, and surface chemistry of nanoparticles on the rubber foam structure and properties still needs further study. On the other hand, the literature is full of blends of thermoplastic foams with several types of thermoplastics being used [ 304 , 305 , 306 , 307 , 308 , 309 ]. However, few studies were found on the foaming of rubber blends or/and thermoplastic/rubber blended foams.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of cellular uniformity is an important parameter to quantify the cellular distribution in different foam zones. 57 However, this study considers a periodic representation of the structure based on a pavement of unit cells with the same cell diameter to focus on the effect only. Whereas the distribution of closed and open cells is considered, in fact, this is a particular and important parameter of the category of mixed cell foams even with periodic approach of REV.…”
Section: Distribution In the Case Of Mixed Cell Foammentioning
confidence: 99%